2004
DOI: 10.1103/physrevlett.92.015501
|View full text |Cite
|
Sign up to set email alerts
|

Twist Elasticity and Anchoring in a Lamellar Nematic Phase

Abstract: Electrooptic measurements were performed on a lamellar nematic phase in which the mesogenic moieties lie in lamellae that are separated by partially perfluorinated side groups. The twist elastic constant K 22 and the quadratic and quartic anchoring strength coefficients are reported. K 22 is found to be considerably smaller than that of typical three-dimensional nematics, a consequence of the greatly weakened interactions between the spatially separated lamellae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…Moreover, de Gennes has discussed theoretically [14] the behaviour of two-dimensional nematics, and has shown that only 'quasi-nematic' order obtains. The orientational correlation n[Q(r 1 )2Q(r 2 )] 2 m diverges for large r 1 2r 2 , where Q is the in-plane azimuthal orientation of the director n. The compound mpp88 clearly is not a two-dimensional system, as the mesogenic layers interact, if only weakly [9]. Nevertheless, the apparent continuous rise in Dn so at the Lam-N transition is intriguing, and requires further investigation.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Moreover, de Gennes has discussed theoretically [14] the behaviour of two-dimensional nematics, and has shown that only 'quasi-nematic' order obtains. The orientational correlation n[Q(r 1 )2Q(r 2 )] 2 m diverges for large r 1 2r 2 , where Q is the in-plane azimuthal orientation of the director n. The compound mpp88 clearly is not a two-dimensional system, as the mesogenic layers interact, if only weakly [9]. Nevertheless, the apparent continuous rise in Dn so at the Lam-N transition is intriguing, and requires further investigation.…”
Section: Discussionmentioning
confidence: 88%
“…With decreasing temperature the mesogenic director profile becomes more peaked along the shearing direction, and the system becomes more strongly biaxial with n s ?n o ?n p . Owing to the relative smallness of Dn so it may be that our previous estimate for the dielectric anisotropy De was too large [9]. Had we used a smaller De we would have calculated yet a smaller twist elastic constant K 22 for the Lam-N phase, indicating an even greater difference from typical 3D nematic behaviour.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Unlike the usual smectic phases (figure 5a) formed by rod-like molecules without lateral chains, in these lamellar phases, the rod-like cores are oriented parallel to the layer plane (denoted as Lam phases) [7,33,34,37,38,53,54]. In the two lamellar phases occurring adjacent to the polygonal cylinder phases (Lam Sm and Lam N ), the biphenyl cores remain parallel to the layer planes and retain in-plane positional and orientational order (Lam Sm , figure 5k) or only orientational order (Lam N , figure 5l ), before the in-plane molecular order is completely lost in the Lam Iso phase occurring at higher temperature or for longer side chain lengths (figure 5m) [53][54][55]. These Lam phases are of significant interest for condensed matter physics in general, as they offer the possibility to investigate phase transitions in quasi-two-dimensional systems [55].…”
Section: Giant Cylinder Honeycombs and Laminated Phasesmentioning
confidence: 99%
“…Im Unterschied zu gewöhnlichen smektischen Phasen sind in den Lam N ‐ und Lam Sm ‐Phasen die π‐konjugierten stäbchenförmigen Molekülsegmente parallel zu den Schichtebenen angeordnet 270. 276, 286, 288291, 305, 306 In diesen Schichten können die stäbchenförmigen Segmente eine isotrope, eine orientierungsferngeordnete (2D‐nematische) oder eine orientierungs‐ und positionsferngeordnete (2D‐smektische) Ordnung annehmen, was zu den dreidimensionalen Lam Iso ‐, Lam N ‐ und Lam Sm ‐Phasen führt. In den Lam Sm ‐ (Abbildung 35 k) und Lam N ‐Phasen (Abbildung 35 l) findet eine Korrelation der Richtung der aromatischen Kernstrukturen benachbarter Schichten statt, was zu biaxial smektischen Phasen führt, wohingegen die Lam Iso ‐Phase (Abbildung 35 m) optisch einachsig ist und daher als ein spezieller Typ von SmA‐Phasen ohne Vorzugsorientierung der stäbchenförmigen Einheiten betrachtet werden kann 306.…”
Section: Komplexe Kompartimentierungsmuster T‐ Und X‐förmiger Polyunclassified